2015
DOI: 10.3109/03009742.2015.1055796
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related disease in Italy: clinical features and outcomes of a large cohort of patients

Abstract: IgG4-RD is an elusive inflammatory disease to be considered in the differential diagnosis of isolated or multiple tumefactive lesions. Long-term disease control can be achieved with corticosteroids and immunosuppressive drugs in the majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
131
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(150 citation statements)
references
References 40 publications
15
131
2
2
Order By: Relevance
“…After combination of our patients with all other published cases of IgG4-RD from Hong Kong, we analysed 104 cases comprising predominantly older men (mean age, 62 ± 13 years; male-to-female ratio=3:1), which is consistent with other reports. [19][20][21][22] Over 95% of patients had serum IgG4 level of >135 mg/dL and an IgG4:IgG ratio of >8%. Although these cut-offs are often quoted in the diagnostic criteria for IgG4-RD, 4,23 it is important to note that elevated serum IgG4 levels can be seen in a variety of other conditions such as malignancies, infections, or autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After combination of our patients with all other published cases of IgG4-RD from Hong Kong, we analysed 104 cases comprising predominantly older men (mean age, 62 ± 13 years; male-to-female ratio=3:1), which is consistent with other reports. [19][20][21][22] Over 95% of patients had serum IgG4 level of >135 mg/dL and an IgG4:IgG ratio of >8%. Although these cut-offs are often quoted in the diagnostic criteria for IgG4-RD, 4,23 it is important to note that elevated serum IgG4 levels can be seen in a variety of other conditions such as malignancies, infections, or autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the demographics, clinical features, and treatment modalities in comparison to other cohorts is shown in Table 1. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] The most common organ systems involved were HBP system (40.4%), salivary gland (33.7%), lymph node (29.8%), and eye (19.2%). A Venn diagram of these most common involved systems from the combined cohort is shown in the Figure. …”
Section: Demographics Clinical Features and Treatment Modalitiesmentioning
confidence: 99%
“…In all studies, neurological disease was relatively rare, although cases of pituitary, meningeal and peripheral nervous system involvement were reported. In two smaller European studies, one from Spain and the other one from Italy, pachymeningitis was the only reported neurological manifestation—2/55 (4%) and 3/41 (7%), respectively [36, 37]. …”
Section: Epidemiologymentioning
confidence: 99%
“…Although the biopsy rate is relatively low, it is similar to other cohorts; for example, in an Italy cohort, 15/41 cases (36.6%) were diagnosed as possible IgG4-RD. 26 In conclusion, glucocorticoid is an effective drug in remission induction of IgG4-RD. Our results showed that there were no statistically significant differences in the efficacy and safety between high and medium doses of glucocorticoid in the remission treatment of IgG4-RD patients.…”
Section: -13mentioning
confidence: 89%